A Step Today Can be a Giant Leap Tomorrow - COVID-19 Management Lesson From the Developing World - Bhandari, Sudhir; Grover, Mohnish; Bhargava, Shruti (Scripta Medica, 2021)
Background: Although India is relatively better resourced as compared with other low middle income countries in several aspects, it shares several chal- lenges and vulnerabilities like high population, resource constraints (limited number of hospital beds, skilled healthcare personnel, intensive care units) and socioeconomic milieu, and it is important that these resources are spent wise- ly to maximise lives saved and minimise disruption to health services for all COVID-19 patients. Hence for dealing with this pandemic quickly and efficiently, a centre which could be set up urgently at a low cost for efficient oxygen triage was needed and thus cater to the sudden enormous load of patients who were unnecessarily occupying oxygen beds in hospitals. Methods: This study describes the setting up, management and outcome of sev- en hundred bedded COVID-19 care centre at Jaipur, India, within three days, at low cost, by multidisciplinary efforts of the Government of Rajasthan for effi- cient triage of patients and to share the excessive patient load of the biggest Government medical college of the state. Results: More than 700 patients were successfully managed at the centre with- in a period of one month with a favourable outcome. The perceptions of patients assessed via questionnaire also establish the success of this endeavour in shar- ing the load of hospitals at the peak of the pandemic. Conclusion: This paper describes the positive impact of setting up this COVID-19 care centre, and experience presented in this paper can be utilised as a novel and future oriented solution to address effectively the unprecedented pressure on the healthcare systems, created by the COVID-19 pandemic.